EFEKTIVITAS SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) UNTUK MENURUNKAN PERILAKU MEROKOK PADA MAHASISWA - Komariah, Laila (EMPATHY Jurnal Fakultas Psikologi, 2013)
Â ABSTRACTÂ This study aims is to examine the effectiveness of Spiritual Emotional Freedom Technique (SEFT) for reducing college smoking behavior. Subjects in this study were students in one of universities in Yogyakarta. The subjects of the study were 22 people consisting of 10 people in Experimental Group and 12 people of Control Group. Criteria for the subject is currently still smoking, willing to follow SEFT Â and willingness to fill out the inform consent and not being in therapy or other programs related to smoking. Spiritual Emotional Freedom Technique was used as intervention model. This research used analysis Mann-Whitney Test and Wicolxon Test with a pretest post test control group design. The results of this study showed that there is a significant reduction of studentsâ smoking behavior that are given SEFT. The conclusion of this study is SEFT Â intervention can decrease studentsâ smoking behavior.Keywords: college, smoking behavior, spiritual emotional freedom technique (SEFT). Â